Tinjauan Hukum Terhadap Kewajiban Kapal Asing Dalam Melaksanakan Hak Lintas Damai Di Laut Teritorial Indonesia - Adelia Hartanti; Aliya Az-zahra; Dinda Trisya (GLOBAL SCIENTS PUBLISHER, 2026)
This study examines the obligations of foreign vessels in exercising the right of innocent passage in Indonesian territorial waters, emphasizing the relationship between international and national law. Issues raised include the limitations of foreign vessels' obligations and how Indonesia enforces these regulations without neglecting the principle of freedom of navigation. This study uses a combined approach: normative juridical through a review of UNCLOS 1982 and various national regulations, and an empirical approach through an analysis of law enforcement practices in the field. The study results indicate that foreign vessels are required to sail continuously, refrain from activities that could disrupt security and order, and comply with provisions regarding shipping lanes, environmental protection, and international safety standards. Furthermore, vessels must avoid illegal activities such as unauthorized fishing, research without approval, and actions that have the potential to pollute the sea. In terms of law enforcement, Indonesia involves various institutions such as the Indonesian Navy and Bakamla (Law and Security Agency) to conduct supervision and enforcement, despite jurisdictional limitations stipulated by international law. The findings of this study indicate that although the regulatory framework is quite comprehensive, there are still obstacles in implementation and coordination between institutions. Therefore, strengthening the oversight system and harmonizing regulations is necessary to ensure that the implementation of foreign vessels' obligations is more effective and consistent.